Systematic Literature Review (SLR) : Tantangan dan Peluang Bisnis Online di Era Digital - Siti Fahirah Sihotang; Zuhrinal M. Nawawi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstract This systematic literature review analyzes the challenges and opportunities faced by online businesses in the digital era. The study found that the development of digital technology has created major changes in the business world, opening up new opportunities for entrepreneurs to reach wider markets and improve operational efficiency. However, the digital era also presents challenges, including intense competition, changes in digital platform algorithms, uneven digital infrastructure, and the need for effective digital marketing strategies. On the other hand, great opportunities are available in the form of global market access, lower operational costs, ease of communication with customers, and inconvenience in managing working hours. The results of the study indicate that to succeed in the digital era, online businesses must address challenges such as cybersecurity, personal data protection, and adaptation to rapid technological developments. They must also take advantage of existing opportunities by implementing effective digital marketing strategies, understanding consumer behavior, and building customer trust.